Synthesis of curcumin nanoparticle from Curcuma xanthorrhiza Roxb. extract by solvent-antisolvent precipitation method - Nur Rofiqoh Eviana Putri; Annisa Amalia Ulfah; Yuni Kusumastuti (Jurnal Rekayasa Proses, 2019)
Curcumin is an active compound found in temulawak (Curcuma xanthorrhiza Roxb.) extract which is widely used for biomedical application. However, the utilization of curcumin is still limited due to its properties i.e. hydrophobicity, poor stability, and low water solubility. Modification of curcumin molecule and process optimization during the extraction and purification process is needed to minimize the aforementioned limitations. One of the approaches is producing curcumin in nano size. This present research aims to optimize the synthesis of curcumin nanoparticle from Curcuma xanthorrhiza Roxb. extract using solvent-antisolvent precipitation method. Curcumin colour stability was also enhanced by controlling the pH during raw materials preparation. The obtained curcumin nanoparticle was then characterized using particle size analysis (PSA). Result showed that Curcuma xanthorrhiza Roxb. extract colour could be controlled by maintaining acidic environment. At the pH of 3, yellow colour of extract was obtained, meanwhile at neutral pH, the colour of extract changed into dark brown. PSA result showed that optimum stirring condition of precipitation process was obtained using 500 rpm stirring rate for 45 minutes which resulted in curcumin nanoparticle in the size range of 164.37±3.29 nm. Thus, by controlling the pH of extract at 3 during extraction process and using optimum stirring condition at 500 rpm for 45 minutes during precipitation process, more stable and soluble curcumin was successfully produced.